Three Specific Potential Epitopes That Could Be Recognized by T Cells of Convalescent COVID-19 Patients Were Identified From Spike Protein - Zhang, Yunwen; Yang, Zhengrong; Tang, Mingyuan; Li, Hao; Tang, Tian; Li, Guilian; Zhong, Yifan; Zhang, Xiaomin; Wang, Xiaohui; Wang, Chuan (Frontiers in Immunology, 2022)
The current COVID-19 vaccines are used to prevent viral infection by inducing neutralizing antibody in the body, but according to the existed experience of SARS infection, T cell immunity could provide longer durable protection period than antibody. The research on SARS-CoV-2 specific T cell epitope can provide target antigen for the development and evaluation of COVID-19 vaccines, which is conducive to obtain COVID-19 vaccine that can provide long-term protection. For screening specific T cell epitopes, a SARS-CoV-2 S protein peptide library with a peptide length of 15 amino acids was synthesized. Through flow cytometry to detect percentage of IFN-γ+ T cells after mixed COVID-19 convalescent patients’ peripheral blood mononuclear cell with peptide library, seven peptides (P77, P14, P24, P38, P48, P74 & P84) that can be recognized by the T cells of COVID-19 convalescent patients were found. After excluding the non-specific cross-reactions with unexposed population, three SARS-CoV-2 specific T cell potential epitopes (P38, P48 & P84) were finally screened with the positive reaction rates between 15.4% and 48.0% in COVID-19 convalescent patients. This study also provided the HLA allele information of peptide-positive-response COVID-19 convalescent patients, thus predicting the population coverage of these three potential epitopes. Some HLA alleles showed higher frequency of occurrence in COVID-19 patients than in total Chinese population, but no HLA alleles related to the T cell peptide response and the severity of COVID-19. This research provides three potential T cell epitopes that are helpful for the design and efficacy evaluation of COVID-19 vaccines. The HLA information provided by this research supplies reference significance for subsequent research, such as that to find the relation of HLA genotype with disease susceptibility.